The use of vodcasting in improving students' speaking skills: The use of vodcasting in improving students' speaking skills - Efiyani, Susi Efiyani; Pratiwi, Dyah Sih; Syafiq, Ahmad (ELT-Lectura, 2024)
Media should be included into learning activities to help teachers and students alike understand the information being taught. The purpose of this study is to ascertain whether employing vodcasting may help class X students at SMK 2 Muhammadiyah Bandar Lampung improve their speaking abilities. Experimental research is the term for this kind of study. Data is collected through tests. It is expected that the study findings could be used as reading material and a basis for further relevant research. It is hoped that the results of this research can be used as an important input for schools, especially for vocational school teachers, where the results of this research can be used as a reference in implementing learning media to improve student learning outcomes; b) for junior high school students, the results of this study are able to create meaningful learning so that it has a strong influence in improving learning outcomes and student motivation. Referring to the calculation results of hypothesis testing, the mean pretest value was 71,72 while the mean post-test was 80,59, thus the Ho hypotension result was rejected and Ha was accepted. Looking at the Sig value 0.00 <0.05, it indicates a significant improvement before and after using vodcasting.